2010
DOI: 10.4269/ajtmh.2010.09-0782
|View full text |Cite
|
Sign up to set email alerts
|

Incubation Periods of Yellow Fever Virus

Abstract: Yellow fever virus is a global health threat due to its endemicity in parts of Africa and South America where human infections occur in residents and travelers. To understand yellow fever dynamics, it is critical to characterize the incubation periods of the virus in vector mosquitoes and humans. Here, we compare four statistical models of the yellow fever incubation periods fitted with historical data. The extrinsic incubation period in the urban vector Aedes aegypti was best characterized with a temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 42 publications
4
72
0
1
Order By: Relevance
“…For the IIP, the gamma and log-normal models were similar and there was no clearly favored model. We previously found that the yellow fever virus (YFV) EIP data was best described by a Weibull model, with the log-normal model a close second, and that the YFV IIP was best described as by a log-normal distribution [66]. In all cases, the log-normal model provided the optimal or near-optimal fit out of the models investigated.…”
Section: Discussionmentioning
confidence: 91%
“…For the IIP, the gamma and log-normal models were similar and there was no clearly favored model. We previously found that the yellow fever virus (YFV) EIP data was best described by a Weibull model, with the log-normal model a close second, and that the YFV IIP was best described as by a log-normal distribution [66]. In all cases, the log-normal model provided the optimal or near-optimal fit out of the models investigated.…”
Section: Discussionmentioning
confidence: 91%
“…However, in areas that are already conducive to transmission of mosquito‐borne diseases, warming temperatures might move the environment away from the thermal optimum. Recent experimental and modeling work suggests that these areas could experience range contractions rather than range expansions of vector‐borne diseases owing to this nonlinear relationship between transmission and temperature …”
Section: Arbovirus Transmission In a Changing Worldmentioning
confidence: 99%
“…This has been studied for malaria parasites of rodents 26,48 , birds 2830 , lizards 49 and humans 25,50,51 ; West Nile virus 20 ; dengue virus 19 ; and yellow fever virus 21 . In general, most of these studies show that warming temperatures are associated with a reduction in the development time of the parasite or pathogen.…”
Section: Temperature and Resistancementioning
confidence: 99%
“…Third, research on a wide range of invertebrates demonstrates that small, realistic changes in ambient temperature can significantly shape overall host resistance to a range of parasites by influencing, for example, parasite virulence, development rates, latency periods and clearance rates within the insect (see Supplementary information S1 (table)). Fourth, numerous studies have already found that the development rates of key vector-borne parasites are strongly temperature dependent; this has been shown for dengue virus 19 , West Nile virus 20 , yellow fever virus 21 , chikungunya virus 22 and filarial nematodes 23,24 , as well as human 25 , rodent 26,27 and avian 2830 malaria parasites. The extent to which temperature shapes vector resistance directly, through such effects on parasite biology, or indirectly, through effects on vector immunity, remains largely unexplored.…”
mentioning
confidence: 96%